Pengaruh Dana Pihak Ketiga, Non Performing Financing, Capitaladequacy Ratio dan Return on Asset, terhadap Tingkat Likuiditas - Ervina, Ervina; Aridansari, Anindya (Management Analysis Journal, 2016)
Abstract This study aims to determine the effect of variable Third Party Funds, Non Performing Financing, Capital Adequacy Ratio, Return on Assets ratio level of liquidity as measured by the Financing to Deposit Ratio (FDR). This meant that the company engaged in the field of financial services are able to make optimal policy, so that the level of liquidity and the existence of the company is always evolving. Necessary data is secondary data from the monthly financial reports Baitul Maal Wattamwil "Bondho Tumoto" Semarang 2011-2013. The sampling technique using time series data, in order to obtain a sample of 36 data. The analysis used is multiple linear regression analysis, partial t test with a significant probability of 5%. Besides the classic assumption test including normality test, multicollinearity, heteroscedasticity and autocorrelation test. Based on this research, it is known that the partial test results, the variable ROA Growth in deposits and a significant negative effect, NPF significant negative effect, then CAR significant positive effect on the level of liquidity (FDR). It can be concluded, that the variable Growth in deposits, ROA and CAR significant effect on the level of liquidity (FDR), while the NPF variables no significant effect on the level of liquidity.